2012
DOI: 10.3168/jds.2012-5591
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics between fly, mouse, and cattle identifies genes associated with sire conception rate

Abstract: The decline in reproductive performance in cattle is of major concern to farmers and the dairy industry worldwide. Most fertility studies in cattle have focused on fertility of the cow, whereas the genetics of male fertility have not been thoroughly investigated. The present study hypothesizes that the high conservation of spermatogenesis genes from fly to human implies important roles of these genes in male fertility in cattle. To test this hypothesis, we performed an association analysis between highly conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 29 publications
3
26
0
2
Order By: Relevance
“…However, results of present study are compared with the available sporadic reports in cattle. Li et al (2012) reported the association between spermatogenesis genes including PPP1R11 and sire conception rate (SCR) in US Holstein as a measure of bull fertility. Four SNPs were reported in PPP1R11 gene in which 3 were located in intronic region while 1 SNP located in 5'UTR (untranslated region).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, results of present study are compared with the available sporadic reports in cattle. Li et al (2012) reported the association between spermatogenesis genes including PPP1R11 and sire conception rate (SCR) in US Holstein as a measure of bull fertility. Four SNPs were reported in PPP1R11 gene in which 3 were located in intronic region while 1 SNP located in 5'UTR (untranslated region).…”
Section: Resultsmentioning
confidence: 99%
“…PPP1R11 gene is one of the important fertility related gene which was found to be associated with the sire conception rate (Li et al, 2012;Khatib, 2015). This gene encodes a specific inhibitor of protein phosphatase-1 (PP1) with a differential sensitivity towards the metal-independent and metal-dependent forms of PP1.…”
Section: Introductionmentioning
confidence: 99%
“…Abordagens genômicas comparativas que identificam genes expressos nos testículos têm caracterizado genes com importantes funções na regulação do desenvolvimento espermático em diferentes espécies (murinos, insetos, humanos e bovinos principalmente) [84,85].…”
Section: Genômica Na Predição De Fertilidadeunclassified
“…Both candidate gene [1416] and whole-genome scan [1721] approaches have attempted to identify genomic regions and individual genes responsible for the genetic variation in bull fertility. For instance, two highly conserved spermatogenesis genes, MAP1B and PPP1R11 , were significantly associated with male fertility in Holsteins [16].…”
Section: Introductionmentioning
confidence: 99%